Sistem Kontrol Menghidupkan Lampu Otomatis Menggunakan Sensor Suara FC-04 Berbasis Arduino Uno - Chairil, Slamet; Teuku Radillah; Satria, Budy (The Indonesian Journal of Computer Science, 2023)
The problem that often occurs is forgetting to turn off the lights when you want to leave because you are in a hurry, as a result the lights stay on and there is a waste of electricity. This research was conducted with the aim of designing an Automatic Light Turning Control System Using the FC-04 Sound Sensor Based on Arduino Uno. When the Sound Sensor FC-04 detects the input of two hands clapping, the relay will give current to the light object so that it turns on automatically. The results of the tests that have been carried out are that the Arduino Uno Microcontroller works well for processing data. Testing the FC-04 Sound Sensor with a distance of 50-200 cm from the input in the form of the sound of applause causes the light to turn on as an output that the sensor functions to detect vibration frequency waves. In addition, the relay device also works well as a regulator of the electric power supply for the lamp so that the lamp can turn on or on. So that this tool can help humans turn off the lights so they no longer have to move closer to the lights and press existing buttons to be able to turn on or turn off the lights, but can be controlled through voice commands of applause.